IMPLEMENTASI PROGRAM SEKOLAH ADIWIYATA (STUDI DI SMP NEGERI 17 BANDA ACEH) - Cut Meurah Badriatun Nufus; Daska Azis; Muhammad Hafizul Furqan (Jurnal Samudra Geografi, 2022)
Environmental education is a solution to minimize environmental damage. One of the government's efforts in realizing environmental education is by launching the Adiwiyata program. Adiwiyata as a school program that aims to create good conditions for schools to become places of learning and awareness of school residents in an effort to encourage environmental conservation and sustainable development. The purpose of the Adiwiyata program is to create school citizens who are responsible for protecting and managing the environment through good school governance. The formulation of the research problem is how to implement the Adiwiyata program at SMP Negeri 17 Banda Aceh?. The research method uses a qualitative descriptive method with data collection techniques using interviews and observation sheets. The resource persons are principals, vice principals, Adiwiyata persons in charge and teachers. Data analysis using data triangulation technique. The results showed that the implementation of the Adiwiyata Program at SMPN 17 Banda Aceh had been implemented well. Preparation of environmental management programs in the form of hydroponic plants and waste banks, internalizing the values ​​of environmental care in RPP and Learning, Fostering collaboration with DLHK3, SMK SMTI, and having adequate infrastructure